Evaluasi Pelaksanaan Praktik Pengalaman Lapangan (PPL) II Program Studi Manajemen Pendidikan Islam Fakultas Tarbiyah Dan Ilmu Keguruan (FTIK) Tahun 2017-2018 - Siti Aminah; Ittihadatul Ummah (Jurnal Darussalam: Jurnal Pendidikan, Komunikasi dan Pemikiran Hukum Islam, 2019)
PPL II is one of the infrastructural academic activity which covers practice to teach and other education assignments by guiding, directing, and integrating to fulfill the requirement of professional staff formation in education. The purpose of evaluation of PPL II in Islamic Management Education Program (MPI), Faculty of teacher training and education (FTIK) is to know the level of success in implementing the program that has done and program that will be used in the next period in order to predict, calculate, and manage the implementation of PPL II in increasing the quality of graduate. There are three phases in evaluating of implementation of PPL II in the Islamic Management Education Program FTIK IAIN Jember 2017 – 2018, they are planning, implementing, and evaluating phase. Meanwhile, the student competence evaluation of the PPL II MPI program is focused on teaching and administration practice.